Fall of the Double Eagle : The Battle for Galicia and the Demise of Austria-Hungary - Schindler, John R. (Book collections on Project MUSE., 2015)
"Examination of the Battle for Galicia (23 August-11 September 1914), the most historically and strategically consequential of the Great War's three opening campaigns"--